PM10 and PM2.5 particles as main air pollutants contributing to rising risks of coronary heart disease: a systematic review. Issue 1 (1st January 2017) - Zhao, Yaxue; Cheng, Zhiyuan; Lu, Yongbin; Chang, Xiaoyu; Chan, Cynthia; Bai, Yana; Zhang, Yawei; Cheng, Ning
ABSTRACT: Although air pollutants are associated with both mortality and incidence of coronary heart disease (CHD), further research is needed to determine the relative harm of each type of air pollutant. A systematic review to study the strength of association between an air pollutant and risks of CHD mortality and incidence was performed, 48 relevant cohort and time-series studies that reported the relationship between air pollutants and risks of CHD mortality and incidence were identified and subgroup analyses for PM10 and PM2.5 by age, sex, geographical location, economic development, and study design. The results showed that: particular matter 10 (particular matter ≤ 10 μm in aerodynamic diameter, PM10) and particular matter2.5 (particular matter  ≤ 2.5 μm in aerodynamic diameter, PM2.5) could increase the risk of CHD mortality more than other gaseous pollutants, although most air pollutants could significantly increase the risk of CHD mortality and incidence. The risk of CHD mortality increased 12% (95%CI: 4%, 20%) with a 10 µg/m 3 PM10 increase, which risk was 4 times for sulfur dioxide (SO2 ), 3 times for Nitrogen dioxide (NO2 ) and carbon monoxide (CO), 2 times for ozone (O3 ), and the risk of CHD mortality increased 17% (95%CI: 12%, 22%) a 10 µg/m 3 PM2.5 increase, which risk was 5 times for SO2, 4 times for NO2 and CO, and 3 times for O3 . The risks of CHD mortality and incidence from PM10 and PM2.5 was 2–5 times higher than from other pollutants.